De Quervain thyroiditis in a young boy following hand-foot-mouth disease - Pontipa Engkakul (2018)
de Quervain thyroiditis, also known as subacute thyroiditis, is a self-limited inflammatory disease of the thyroid gland. It is extremely rare in children. The hallmarks for diagnosis are painful thyroid enlargement, elevated inflammatory markers, and decreased uptake of the thyroid gland on thyroid scintigraphy. Viral infection has been proposed to be associated with de Quervain thyroiditis. Coxsackie virus has been reported to be one of the viruses associated with the disease. To our knowledge, childhood de Quervain thyroiditis associated with hand-foot-mouth disease caused by coxsackie infection has never been reported. We report a 2.7-year-old boy who presented with typical features of de Quervain thyroiditis following hand-foot-mouth disease caused by coxsackie B4 infection. He had a brief thyrotoxic phase initially, followed by transient hypothyroid phase and euthyroidism thereafter. His thyroid scintigraphy showed a typical faint uptake at the diagnosis, and an improvement of the thyroid scan and uptake was shown 8 weeks later. He was treated with prednisolone and nearly complete resolution was documented within 2 months. Careful evaluation of the patient led to the correct diagnosis and appropriate management. © 2010 Springer-Verlag.